A cohort study and meta-analysis of the evidence for consideration of Lauren subtype when prescribing adjuvant or palliative chemotherapy for gastric cancer. (July 2020) - Wang, Kunning; Li, Enxiao; Busuttil, Rita A.; Kong, Joseph C.; Pattison, Sharon; Sung, Joseph J. Y.; Yu, Jun; El-Omar, Emad M.; Simpson, Julie A.; Boussioutas, Alex
Background: The association between the survival or efficacy of chemotherapy and the Lauren subtype of gastric cancer (GC) remains unclear. We aimed to clarify whether patients with different Lauren subtypes have different survival after treatment with systemic chemotherapy: intestinal gastric cancer (IGC) patients survived better than patients with mixed type gastric cancer (MGC) or diffuse gastric cancer (DGC) after treatment with systemic chemotherapy. Patients & methods: Relevant studies for the meta-analysis were identified through searching Pubmed, Embase, Cochrane and Ovid up to March 2020. We also included our own prospectively collected cohort of patients that were followed over a 10-year period. Sub-group and sensitivity analyses were also performed. Results: In our prospective cohort, the overall survival (OS) of IGC patients receiving systemic chemotherapy (chemoIGC) [median OS 5.01 years, interquartile range (IQR) 2.63–6.71] was significantly higher than that of DGC patients receiving the same chemotherapy (chemoDGC) (median OS 1.33 years, IQR 0.78–3.33, p  = 0.0001). After adjusting for age, gender and cancer stage, there was a significant difference in OS in patients treated with chemotherapy based on the Lauren classification of GC {hazard ratio (HR) for OS of the IGC versus DGC 0.33, [95% confidence interval (CI), 0.17–0.65; p  < 0.001]}. In the IGC patients, the adjusted HR associated with chemotherapy was 0.26 (95% CI, 0.12–0.56; p  = 0.001), whereas the association was 0.64 (95% CI, 0.30–1.33; p  = 0.23) in the DGC patient group. In our meta-analysis, 33 studies comprising 10, 246 patients treated with systemic chemotherapy (chemoIGC n  = 4888, chemoDGC n  = 5358) met all the selection criteria. While we accounted for much of the heterogeneity in these studies, we found that chemoIGC patients showed significantly improved OS [HR, 0.76 (95% CI, 0.71–0.82); p  < 0.00001] when compared with similarly treated chemoDGC patients. Conclusion: Our results support the consideration of Lauren subtype when prescribing systemic chemotherapy for GC, particularly for MGC or DGC, which may not benefit from chemotherapy. Lauren classification should be considered to stratify chemotherapy regimens to GC patients in future clinical trials, with particular relevance to MGC or DGC, which is more difficult to treat with current regimens.